SPRINGS (CLASSIFICATION, FUNCTION, CAPTURING) - Soulios, G. (Bulletin of the Geological Society of Greece, 2010)
Todd, K (1980) proposed the following definition for springs: “a concentrated discharge of groundwater that emerges on the ground as a stream of water that flows freely”. Spring is distinguished from water leak that is a normally diffused but extended (linear or 2D) slower movement of groundwater towards the ground surface. Uprush is every groundwater emergence on the ground surface or through the bed of water bodies (river, lake, sea). In the context of hydrogeology springs and uprushes in general are in fact “overflows” of aquifers; hence they serve as aquifer discharge mechanisms. Springs emerge at the cross section of groundwater level with the topographic relief. Springs are a strong evidence of rich groundwater potential. A big number of small springs emerging at the margins of basins or the hill slopes are an evidence of a shallow aquifer of low hydraulic conductivity. On the contrary, big springs emerging at the bottom of valleys, i.e. the basic geomorphological level, are an indication of a high potential aquifer characterized by considerable values of hydraulic conductivity.